Effects of turmeric powder on intestinal and biliary functions: The influence of curcuminoids concentration on spontaneous contractility. (December 2022) - Micucci, Matteo; Budriesi, Roberta; Mandrioli, Mara; Tura, Matilde; Corazza, Ivan; Frosini, Maria; Aldini, Rita; Mattioli, Laura Beatrice; Gallina Toschi, Tullia
Graphical abstract: Highlights: Curcuminoid content of two Curcuma longa L. food powders was determined by HPLC. Different curcuminoid content reduced spontaneous contractility. The amount of curcuminoids may be relevant for the formulation of functional foods. Abstract: Two turmeric food powders (C1 and C 2) were studied for curcuminoid content and their effects on the guinea pig intestinal tract in vitro. C1 contained a higher curcuminoid content than C2 (5.22% vs 2.31%). C1 and C2 increased gallbladder (∼10%) and biliary smooth muscle tone (∼15%), without affecting the sphincter of Oddi smooth muscle contractility. C2 was more effective than C1 in lowering ileum tone (–22% vs −37%), whereas the reverse occurred in the colon (-50% vs −20%). Standard Fast Fourier transforms and absolute powers analysis of the frequency bands highlighted that, in the bile duct, C2 induced contractions of higher variability and ampler oscillations of low-frequency waves. At the Oddi sphincter, C1 had a biphasic effect, increasing and then drastically decreasing the oscillations. The same occurred with C2 in the ileum, while both samples reduced the fluctuations in the colon.